Use of pea agar with Tween 80 for Dalmau technique for identification of Candida albicans (Eastern Journal of Medical Sciences, 2017)
Introduction: Candida albicans produces devastating infections with considerable attributable mortality. Identification rests ofDalmau technique using rice extract agar, which is very prone to aerial contamination and drying and breakage. Materials andMethods: We here evaluated pea agar, with and without Tween 80, as medium for Dalmau technique for identifying C. albicansand compared it with rice extract agar. Results: Pea agar with Tween 80 was a very useful medium for identifying C. albicans.Conclusion: Pea agar with Tween 80 can be used for Dalmau technique for C. albicans identification.